The influence of self-assessment as a tool for learning English on language acquisition - Růžičková, Jolana (Univerzita Pardubice, 2024)
This bachelor thesis deals with the self-assessment of learners learning a foreign language, specifically English, focusing on its connection to their motivation for learning. This thesis aims to determine the current influence of self-assessment on English language learning, focusing on the relationship between self-assessment and the learner's motivation. Initially, the concept of a learner, specifically the group targeted by this literature review, is introduced. Furthermore, the terms motivation, evaluation, and self-assessment are briefly explained. The thesis is divided into two parts – theoretical and practical, with the latter presented as a literature review. The theoretical part consists of basic concepts that are applied in the practical section.
Vliv sebehodnocení jako nástroje učení se cizího jazyka na osvojení tohoto jazyka
Keywords: literature review; self-assessment; motivation; learning; learner; English language; přehledová studie; sebehodnocení; motivace; učení; anglický jazyk